Intentions and Cooperative Activity: Explaining Cooperation in Light of Bratman’s Notion of Shared Intention (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
This paper focuses on one of the major controversies about the explanation of collective action. The discussion revolves around the possibility of ascribing intentions to groups, understanding these intentions as distinct from the mere sum of group members’ individual intentions. In the literature on this subject we can identify two main lines of explanation of collective intentions: one that reduces group intentions to the sum of individual intentions and another that appeals, through a variety of strategies, to some kind of plural subject or collective consciousness. Based on the notion of shared intention, Michael Bratman has offered an interesting and successful alternative to both views. My goal is to present and analyse that notion of shared intention, explaining why it is interesting to consider Bratman’s proposal.